Home: Architecture of Memory - Ernst, Sophie (West Bretton Yorkshire sculpture park, 2012)
YSP presents the first solo exhibition in the UK by Sophie Ernst. HOME is a major ongoing project confronting political turmoil and displacement with individual memories of home and ideal places. Ernst interviews people forced to leave their homes due to political upheaval, such as during the Partition of South Asia in 1947, and builds an architectural model of the houses they describe. She then projects onto this sculpture video footage of the person's hands as they describe their memory of that building, transforming the inanimate object into a virtually inhabited space, and ascribing a profound intimacy.